Pengembangan Media Pembelajaran Dosean Pada Materi ASEAN - Ainun Fitri Yadi; Ima Rahmawati; Rusdiono (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
This research is motivated by a problem which is known that there are still students who are not active in class VI in Social Sciences (IPS) subjects on ASEAN material, because IPS is a subject that has a lot of memorization and in the ASEAN material there are many country names. , figures and years that make students have difficulty with material about ASEAN so that domino cards are needed to concretize the material in these subjects. The purpose of this research is to develop educational game-based learning media DOSEAN (Domino Asean) on the material contained in the thematic books of SD/MI grade 6 theme 1